2002
DOI: 10.1074/jbc.m206223200
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Helix 7 Tyrosine Acts as a Multistate Conformational Switch in the 5HT2C Receptor

Abstract: Studies in many rhodopsin-like G-protein-coupled receptors are providing a general scheme of the structural processes underlying receptor activation. Microdomains in several receptors have been identified that appear to function as activation switches. However, evidence is emerging that these receptor proteins exist in multiple conformational states. To study the molecular control of this switching process, we investigated the function of a microdomain involving the conserved helix 7 tyrosine in the serotonin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(49 citation statements)
references
References 77 publications
(73 reference statements)
4
45
0
Order By: Relevance
“…Several lines of evidence suggest a structural rearrangement of H8 after receptor activation (15,(26)(27)(28)(29)(30)(31)(32). Here, we showed that the release of the constraint on the NPxxY(x) 5,6 F region imposed by the Y306-F313 interaction occurs during the Meta I͞Meta II transition as unveiled by UV-visible spectroscopy.…”
Section: Conformational Changes In the Npxxy(x)56f Region After Recesupporting
confidence: 57%
See 1 more Smart Citation
“…Several lines of evidence suggest a structural rearrangement of H8 after receptor activation (15,(26)(27)(28)(29)(30)(31)(32). Here, we showed that the release of the constraint on the NPxxY(x) 5,6 F region imposed by the Y306-F313 interaction occurs during the Meta I͞Meta II transition as unveiled by UV-visible spectroscopy.…”
Section: Conformational Changes In the Npxxy(x)56f Region After Recesupporting
confidence: 57%
“…Mutations in the NPxxY(x) 5,6 F motif affect receptor expression, ligand affinity, receptor sequestration, heterotrimeric G protein coupling, and association with the small G proteins ARF and RhoA (for example, see refs. [13][14][15][16].…”
mentioning
confidence: 99%
“…Because conservation of the pentapeptide sequence implies an important structural or functional role, this motif has been examined by mutagenesis studies in several GPCRs. These mutations affected receptor affinity (5,7,8), signaling (3,5,6,9), sequestration (4, 13), and internalization of GPCRs (12) but to quite different extents, depending on the receptor under study. This may, in part, be reflective of the microenvironment surrounding this motif in the respective receptor sequence, the assays applied, or the cells used for ex- pression.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most highly conserved motifs, together with the E/DRY sequence at the cytosolic end of transmembrane domain-3, is the NPXXY sequence (where X usually represents a hydrophobic residue and N is rarely exchanged against D) located at the C terminus of transmembrane domain-7. The results of these mutagenesis studies implicate this motif in the signaling, sequestration, and internalization of many GPCRs (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Agonist binding or constitutively active mutations disrupt a series of constraining intramolecular interactions that keep the receptor in the inactive conformation. Recently identified constraints within the transmembrane domain are i) the conformational transition of Trp of the CWxP motif in TM 6 (11,12), ii) the interaction of Asn of the NPxxY motif in TM 7 with either residues located in TM 6 (13) or the backbone of TM 6 through a water molecule (14), iii) the ionic lock between Arg of the highly conserved (D/E)RY motif in TM 3 and a partly conserved Asp/Glu residue in the cytoplasmic end of TM 6 (15), and iv) the aromatic-aromatic interaction between Tyr of the NPxxY motif in TM 7 and an aromatic residue located in HX 8 (16,17). Release of these constraints induce rigid body motions of several if not all transmembrane helices (18,19).…”
mentioning
confidence: 99%